Secret Agent Jack Stalwart. [book 6], The Pursuit of the Ivory Poachers : Kenya - Singer Hunt, Elizabeth (Red Fox, 2006)
Secret Agent Jack Stalwart is about to decipher a code from his missing brother, Max, when he's called on a mission to Kenya. Someone has been killing precious African elephants for their tusks. Can Jack find the poachers and stop them before they strike again